2018
DOI: 10.1002/jbm.a.36488
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytotoxicity and antimicrobial activity of an injectable bone substitute of carrageenan and nano hydroxyapatite

Abstract: How to cite this article: González Ocampo JI, Bassous N, Ossa Orozco CP, Webster TJ. 2018. Evaluation of cytotoxicity and antimicrobial activity of an injectable bone substitute of carrageenan and nano hydroxyapatite. J Biomed Mater Res Part A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…CGs are applied in various pharmaceutical formulations, including tablets [ 106 , 108 ], suppositories [ 109 , 110 ], films [ 111 ], fast-dissolving inserts (FDIs) [ 63 ], beads [ 112 , 113 ], pellets [ 114 , 115 , 116 ], microparticles [ 117 , 118 , 119 ], nanoparticles [ 120 , 121 , 122 , 123 , 124 , 125 ], inhalable systems, injectables [ 126 ], and hydrogels [ 127 , 128 , 129 ]. In addition, recent studies have shown that CGs are promising candidates in tissue engineering, thanks to their similarity to native glycosaminoglycans [ 127 , 128 , 130 , 131 ].…”
Section: Carrageenan In Biomedical Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…CGs are applied in various pharmaceutical formulations, including tablets [ 106 , 108 ], suppositories [ 109 , 110 ], films [ 111 ], fast-dissolving inserts (FDIs) [ 63 ], beads [ 112 , 113 ], pellets [ 114 , 115 , 116 ], microparticles [ 117 , 118 , 119 ], nanoparticles [ 120 , 121 , 122 , 123 , 124 , 125 ], inhalable systems, injectables [ 126 ], and hydrogels [ 127 , 128 , 129 ]. In addition, recent studies have shown that CGs are promising candidates in tissue engineering, thanks to their similarity to native glycosaminoglycans [ 127 , 128 , 130 , 131 ].…”
Section: Carrageenan In Biomedical Applicationsmentioning
confidence: 99%
“…CGs have also been considered in the development of an injectable bone substitute (IBS) [ 126 , 131 ]. Based on CG and nanohydroxyapatite (nHA), the formulations that consisted of 1%, 1.5%, and 2.5% CG and 60% nHA were evaluated, in order to determine its interactions with human osteoblasts.…”
Section: Carrageenan In Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytotoxicity of micrometer-sized AgNPs was minimized by immobilizing them in carrageenan gel retaining the antibacterial property [ 85 ]. A study based on an injectable composite of carrageenan and nanoscale hydroxyapatite as an injectable bone substitute showed good adhesion properties with no cytotoxicity in vitro, as shown in Figure 6 [ 116 ]. The nanocomposite also exhibited antibacterial effect indicating its potential to restrict biofilm formation.…”
Section: Reviewmentioning
confidence: 99%
“…(C) The nanocomposite shows osteoblast cytotoxicity tests in cell lines (L02 and L929). Adapted from [ 116 ], J. I. González Ocampo et al, “Evaluation of cytotoxicity and antimicrobial activity of an injectable bone substitute of carrageenan and nano hydroxyapatite”, J. Biomed. Mater.…”
Section: Reviewmentioning
confidence: 99%